2015
DOI: 10.1515/romneu-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic acute bilateral facial nerve palsy - a management dilemma

Abstract: Acute bilateral facial nerve paralysis is a rare clinical entity, and its management remains very controversial (operative or conservative). Here we are presenting a case of acute onset bilateral facial nerve palsy following head injury with bilateral temporal bone fracture with clinico-radiographic contrary. Patient was managed conservatively with complete recovery. By this article, authors want to stress on combining clinical examination and radiological findings for decision making of this rare entity and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In this case, the facial paralysis was managed conservatively with physical therapy. Kumar et al 15 recommended that all patients of facial nerve palsy should be given conservative management first, albeit, if there was no recovery at the end of three months then surgery might be considered. Turel et al 16 in their study concluded that most patients of posttraumatic facial nerve injuries recovered with conservative treatment and time.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the facial paralysis was managed conservatively with physical therapy. Kumar et al 15 recommended that all patients of facial nerve palsy should be given conservative management first, albeit, if there was no recovery at the end of three months then surgery might be considered. Turel et al 16 in their study concluded that most patients of posttraumatic facial nerve injuries recovered with conservative treatment and time.…”
Section: Discussionmentioning
confidence: 99%